New decision systems in the VUCA world - Minciu Mihaela (Management şi Marketing, 2020)
In a turbulent economic environment, marked by multiple challenges and changes at every step, organizations must adapt their management system, in order to maintain or even increase their productivity, as well as their competitive advantage. All the activities carried out within an organization are based on a series of managerial decisions, dependent on each other, by which the objectives and the modalities of action are determined, ensuring the economic-financial balance. Frequently, the activities carried out within an organization are changing, as the circumstances and characteristics of the business environment increasingly suffers transformations, thus it is necessary that the decision-making processes be updated. Therefore, the employees of the companies must be prepared to organize their activity in a volatile, uncertain, complex and ambiguous world - the VUCA world. Above the decision environment, are manifested a series of indirect and direct influences (interdependent variables, constraints and limit situations) that affect the result of the decisions adopted within the different levels of management in organizations. Thus, the present paper aims to determine and investigate the factors that influence the characteristics of the decision situations, regardless of the type of decisions adopted within an organization. The present study consists in analyzing the results obtained after applying an online questionnaire to researchers from Doctoral Schools and students of Project Management, from the Bucharest University of Economic Studies, who work in different areas of activity. After the statistical processing of the results obtained regarding the decision systems in the VUCA world, this paper aims to highlight the most important changes that occur in decision-making processes representing a key element for organizations in which managers have to make decisions on a daily basis, in order to ensure the economic performance, despite all the disruptions that occur.